Power Control Imperfection in CDMA Systems with Adaptive Antennas - Hrudkay, K.; Wieser, V. (Radioengineering Society, 2002)
This paper deals with a simulation of cellular CDMA system using base station adaptive antennas. The model assumes two tiers area, four types of antennas, lognormal shadowing corresponding to three types of environments and perfect power control or two values of power control error, respectively. The capacity of system in up-link is evaluated by a number of mobile stations with higher signal to interference ratio than threshold with given outage probability.
Keywords: CDMA; cellular; adaptive antennas; shadowing; power control; capacity